Legal Pluralism and the Transformation of Islamic Inheritance Law: A Study of Sasak Customary Practices in Indonesia - Yusmita, Yusmita; Sitorus, Iwan Romadhan; Shesa, Laras; Septiana Rachman, Evy; Lumatus Sa'adah, Sri (Institut Agama Islam Negeri Curup, 2025)
This study examines the dynamics of legal pluralism and the transformation of Islamic inheritance law within the indigenous Sasak community of Indonesia. Its primary objective is to explore how the deeply entrenched patrilineal tradition, which privileges sons in the transmission of land and core family assets, interacts with the proportional distribution mandated by Islamic inheritance law (farā’iḍ), a system that explicitly recognizes the rights of female heirs. Employing a qualitative approach rooted in socio-legal empiricism, the research draws on in-depth interviews with customary leaders, Sasak community members, and scholars of Islamic jurisprudence, complemented by documentary analysis of national legal instruments and classical fiqh literature. Findings reveal that, although patrilineal practice remains predominant, a discernible shift in values is underway toward greater adherence to Islamic inheritance principles, particularly among younger generations and families with higher educational attainment. Socio-economic change, modernization, and growing awareness of gender justice have collectively fuelled this transformation, even as resistance persists among traditional elders who regard patrilineal inheritance as an indispensable marker of cultural identity. The study concludes that these developments exemplify the inherent dynamism of Islamic law through processes of renewal (tajdīd) and selective adaptation (takhayyur). Achieving a just, gender-inclusive inheritance system with broad social legitimacy in the Indonesian context ultimately requires thoughtful harmonization among Islamic inheritance norms, local customary traditions, and the national legal framework.